Can a supernova bang twice? - Schaffner-Bielich, Jürgen; Fischer, Tobias; Hempel, Matthias; Matthias, Liebendörfer; Pagliara, Giuseppe; Sagert, Irina (Progress of theoretical physics. Supplement, 2010)
The implications of a QCD phase transition at high temperatures and densities for core-collapse supernovae are discussed. For a strong first order phase transition to quark matter, various scenarios have been put forward in the literature. Here, detailed numerical simulations including neutrino transport are presented, where it is found that a second shock wave due to the QCD phase transition emerges shortly after bounce. It is demonstrated that such a supernova banging twice results in a second peak in the antineutrino spectrum. This second peak is clearly detectable in present neutrino detectors for a galactic supernova.